Systems, Software and Services Process Improvement 23rd European Conference, EuroSPI 2016, Graz, Austria, September 14-16, 2016, Proceedings - Kreiner, Christian; O'Connor, Rory V.; Poth, Alexander; Messnarz, Richard (Communications in Computer and Information Science, 2016)
This volume constitutes the refereed proceedings of the 23rd EuroSPI conference, held in Graz, Austria, in September 2016. The 15 revised full papers presented together with 14 selected key notes and workshop papers were carefully reviewed and selected from 51 submissions. They are organized in topical sections on SPI and the ISO/IEC 29110 standard; communication and team issues in SPI; SPI and assessment; SPI in secure and safety critical environments; SPI initiatives; GamifySPI; functional safety; supporting innovation and improvement.